Economics, Sustainable Growth, and Community. (1st August 1993) - Parker, Kelly
Sustainable growth is emerging as a normative concept in recent work in economics and environmental philosophy. This paper examines several kinds of growth, seeking to identify a sustainable form which could be adopted as normative for human society. The conceptions of growth expressed in standard economic theory, in the writings of John Dewey, and in population biology, each suggest particular accounts of how the lives of individuals and communities ought to be lived. I argue that, while absolute sustainablity is not possible, the latter two conceptions together suggest a regulative ideal of sustainable growth which is acceptable at the social level, and which encourages the development of genuine community.